Hubungan antara Stigma Sosial dengan Psychological Well-being pada Ibu yang memiliki Anak dengan Disabilitas - Abelia Ocma Safira; Free Dirga Dwatra (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study aims to determine the relationship between social stigma and psychological well-being in mothers of children with disabilities in Padang City. The background of this study is based on the negative labeling and discrimination often experienced by these mothers, which can affect their mental health and parenting skills in raising children with special needs. The social stigma attached to families with children with disabilities often makes mothers feel protected, experience emotional stress, and decrease self-confidence. This condition has the potential to cause prolonged stress that ultimately has a negative impact on their psychological well-being. This study used a quantitative method with a purposive sampling technique, where 93 respondents mothers of children with disabilities in Padang City were selected as research participants. Data collection was carried out using an instrument in the form of a Likert scale that has been tested for validity and reliability. This scale measures two main variables: the level of social stigma experienced by mothers and the level of psychological well-being, which includes aspects such as happiness, life satisfaction, and overall mental health. The results showed that 30.1% of these mothers reported a high level of psychological well-being, while 34.4% reported a low level of social stigma. These findings indicate relatively good psychological well-being, although some mothers still experience social stigma. Statistical analysis using correlation revealed a significant negative relationship between social stigma and psychological well-being. This means that the lower the level of social stigma experienced by mothers, the higher their level of psychological well-being. These findings confirm that reducing social stigma and discrimination against mothers with children with disabilities is crucial for improving their quality of life.